Design of a centrifugal flow chamber in plastic materials to replace traditional drop chambers in high gradient sewers (2024)
Centrifugal flow chambers are a proposed methodology for replacing traditional drop chambers in high and low gradient sewer systems due to their ability to dissipate energy in a compact space. The purpose of this thesis is to test three inlet configurations for this type of chamber and compare the energy dissipation results with those of previously studied inlet types. The goal is to determine the most optimal configuration. After data collection and processing, which evaluate the energy dissipated through impact and friction, the most suitable configuration is identified. The conclusion is that the type of inlet does not significantly influence the energy dissipation process, as all inlet types used result in energy dissipation rates exceeding 89%, indicating that they are suitable for use in any type of sewer system.